PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DI LEMBAGA PENDIDIKAN DAN PENGEMBANGAN PROFESI INDONESIA (LP3I) BUSINESS COLLEGE MALANG - Sudirman, Sudirman (J-PAI: Jurnal Pendidikan Agama Islam, 2018)
Abstract: The needs of Islamic education in universities is very high, meaning that students are very important for religious education is provided mainly in the field of belief and morals. The Lecturer of Islamic religion in LP3I-Business College e Unfortunate problem encountered is a lot to know about the science of business science and the world of work to mengkolaborasi with Islamic religious education courses (PAI). Lecturer of Islam that teaches Islamic education (PAI) in LP3I-Business College to take steps in teaching PAI, namely: 1. Choose the mosque as a place of teaching and learning from on set in the classroom as the other courses. 2. Require the student to establish the prayer dhuha and recite the Qur'an (verses) before the course begins. 3. Divide the group class discussion in accordance with the material PAI (Islamic education) in LP3I Business College syllabus hapless then presented by the method of discussion in order to make students more easily understand the religious values of Islam especially problem beliefs and morals. 4. Hold the oral exam (reading Quran) and the practice of the prayer at the end of the meeting, in addition there are middle test and final test, the goal to be more intensive.Key Words: Islamic Education, LP3I, Business College